Commodity risk assessment of Berberis thunbergii potted plants from Turkey. (30th June 2022) - ,; Bragard, Claude; Baptista, Paula; Chatzivassiliou, Elisavet; Di Serio, Francesco; Gonthier, Paolo; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; et al.
Abstract: The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in the Commission Implementing Regulation (EU) 2018/2019 as 'High‐risk plants, plant products and other objects'. This Scientific Opinion covers plant health risks posed by potted plants (2–3 years old) of Berberis thunbergii produced in nurseries and imported into the EU from Turkey, taking into account the available scientific information, including the technical information provided by the NPPO of Turkey. The relevance of any pest for this Opinion was based on evidence following defined criteria. Two species, the EU‐quarantine pest Bemisia tabaci and the non‐regulated pest Malacosoma parallela, fulfilled the relevant criteria and were selected for further evaluation. For these pests, the risk mitigation measures proposed in the technical dossier from Turkey were evaluated taking into account the possible limiting factors. For these pests, an expert judgement is given on the likelihood of pest freedom taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. The estimated degree of pest freedom varies among the pests evaluated, with B. tabaci being the pest most frequently expected on the imported plants. The Expert Knowledge Elicitation indicated, with 95% certainty, that between 9, 928 and 10, 000 plants per 10, 000 would be free of B. tabaci . The role of Berberis thunbergii as possible host of Puccinia spp. is discussed in the body of the opinion.